Nursing Interventions Through Time : History as Evidence - D'Antonio, Patricia; Lewenson, Sandra (Springer Pub. Co., 2010)
Designated a Doody's Core Title!. "This is a must-read for nurses who are interested in where nursing has been and what nurses have done to get to the present day." Score: 94, 4 stars. --Doody's. Nursing has a rich history that consistently informs contemporary practice and standards. This book, by examining pivotal historical interventions across the spectrum of clinical care, allows nurses of today to incorporate the wisdom of the past into their own daily work. Maternal-child health programs, palliative care, tuberculosis, medications, pediatric care, and diabetes care, and more.